Determination of Manning’s Roughness Coefficient in Bijayapur Irrigation Canal, Kaski, Nepal - Gautam, Arjun (Himalayan Journal of Applied Science and Engineering, 2021)
The discharge in irrigation canal is to be determined for the proper allocation of water to the fields as per the crop-water requirement. Manning’s roughness coefficient is one of the major important parameters for estimating discharge in open channel. The purpose of this research is to determine Manning’s roughness coefficient in open channel flow by means of measuring velocity, cross-section, bed slope using Manning’s equation. It also discusses how it varies along with various aspects of channel geometry and draws useful conclusion from the analysis. The investigation was carried out in the Bijayapur Irrigation System which is situated in Kaski district of Nepal. The velocity was measured using current-meter and discharge was calculated from the area velocity methods. Roughness coefficient was calculated using the Manning’s equations for the uniform flow in open channel. The average value of Manning’s roughness coefficient at Sakneri and Bijayapur computed from this study was found 0.028 and 0.037, respectively. The roughness coefficient, however, being a parameter representing the integrated effects of the channel cross-sectional resistance, the result of this study shows the higher value of roughness coefficient for the material (cement rubble masonry) used in the construction of canal. The higher value of roughness coefficient might be due to uneven bed and poor condition of banks as observed during the study. The greater value of roughness coefficient definitely reduces discharge which leads to the tail end deprivation in the command area.